Androgen-Binding Protein (Abp) Evolutionary History: Has Positive Selection Caused Fixation of Different Paralogs in Different Taxa of the Genus Mus?. (23rd September 2021) - Karn, Robert C; Yazdanifar, Golbahar; Pezer, Željka; Boursot, Pierre; Laukaitis, Christina M
Abstract: Comparison of the androgen-binding protein ( Abp ) gene regions of six Mus genomes provides insights into the evolutionary history of this large murid rodent gene family. We identified 206 unique Abp sequences and mapped their physical relationships. At least 48 are duplicated and thus present in more than two identical copies. All six taxa have substantially elevated LINE1 densities in Abp regions compared with flanking regions, similar to levels in mouse and rat genomes, although nonallelic homologous recombination seems to have only occurred in Mus musculus domesticus . Phylogenetic and structural relationships support the hypothesis that the extensive Abp expansion began in an ancestor of the genus Mus . We also found duplicated Abpa27 's in two taxa, suggesting that previously reported selection on a27 alleles may have actually detected selection on haplotypes wherein different paralogs were lost in each. Other studies reported that a27 gene and species trees were incongruent, likely because of homoplasy. However, L1MC3 phylogenies, supposed to be homoplasy-free compared with coding regions, support our paralog hypothesis because the L1MC3 phylogeny was congruent with the a27 topology. This paralog hypothesis provides an alternative explanation for the origin of the a27 gene that is suggested to be fixed in the three different subspecies of Mus musculus and to mediate sexual selection and incipient reinforcement between at least two of them. Finally, we ask why there are so many Abp genes, especially given the high frequency of pseudogenes and suggest that relaxed selection operates over a large part of the gene clusters.